Exchange Rate Developments and Policies in the Caucasus and Central Asia - Horton, Mark (Departmental Papers; Departmental Paper ;, 2016)
Since late 2014, exchange rates (ERs) and ER regimes of the Caucasus and Central Asia (CCA) countries have come under strong pressure. This reflects the decline of oil and other commodity prices, weaker growth in Russia and China, depreciation of the Russian ruble, and appreciation of the U.S. dollar, to which CCA currencies have historically been linked. Weaker fiscal and current account balances and increased dollarization have complicated the picture. CCA countries entered this period with closely managed ER regimes and, in many cases, currencies assessed by IMF staff to be overvalued. CCA central banks have price stability as their main policy objective, and most have relied on ER stability to achieve this objective. Thus, the first policy response involved intervention in local foreign exchange (FX) markets, often with limited communication. In this context, the IMF staff has reviewed ER policy advice and implementation strategies for CCA countries.